Kebijakan Penegakan Hukum Tindak Pidana Terhadap Pencucian Uang (Money Laundering) Di Indonesia - Shiva, Khadizah Aliyah; Putry, Salsabila Afifany Susanta; Hosnah, Asmak UI (Faculty of Law, Universitas Pattimura, 2024)
Introductioan: Law enforcement against money laundering in Indonesia is a major challenge, given the complexity of cases, linkages with other crimes, and efforts by perpetrators to hide the proceeds of crime. Effective policies are needed to ensure the integrity of the financial system, prevent state losses, and strengthen coordination between law enforcement agencies.Purposes of the Research: The purpose of this article is to analyze the effectiveness of policies, obstacles to law enforcement, and provide recommendations to strengthen the handling of money laundering in Indonesia.Methods of the Research: Using normative legal research methods by using the main focus on laws and regulations such as Law No. 8 of 2010.Results of the Research: The results show that Law Number 8 Year 2010 provides a strong legal basis for the prevention and eradication of money laundering in Indonesia. The existence of institutions such as PPATK is a key factor in detecting and reporting suspicious transactions. However, the effective implementation of this law is often constrained by weak coordination between law enforcement agencies, lack of technical understanding of money laundering cases, and limited human resources and technology. In addition, tracing assets hidden overseas remains a major challenge, despite international cooperation efforts.